Andando pelo vale da sombra da morte: um estudo sobre o cotidiano do “estar” no Hospital Napoleão Laureano - Lima, Rosangela de Araujo (2009)
This paper aims to analyze the daily routine of the Hospital Napoleão Laureano, in João Pessoa, which was projected for the treatment of cancer. It has its focus on the death caused by that disease. Death seen through the view of Out of Therapeutic Possibilities patients, their caretakers and the team of professionals that provides them with assistance more closely: medical professionals, nurses and therapists. The study is eminently qualitative, with the use of ethnography, methodological and theoretical compound. The results show a vigorous denial of death by the triad involved, patients, caretakers and health crew; the loneliness of OTP patients and the usage of foolish treatments, as well as the crystallization of the hospital routine with few pattern change possibilities of the referred reality. The team refuses the contact with OTP patients and the caretakers proceed with a social rule based on the repetition of a monotone speech that the patient’s healing will come: it is almost a social formality. However, through associative procedures patients are revealed of their real conditions and all share the so called pact of silence.